IoT Based Smart Home with Monitoring and Control System - Muhammad Zhareef Aimullah Sabri,; Nor Aira Zambri,; Sim Sy Yi,; Farahiyah Mustafa, (Progress in Engineering Application and Technology, 2022)
The issue regarding the energy consumption that often heard is the waste of energy when electrical appliances are switched ON even it is unused. This is due to the human negligence where the user usually does not aware and forget to turn off unused electric appliances especially during morning when rushing for work. The overconsumption of energy will become a waste that might increases the electricity bills and also a possibility of short circuit and fire due to the overheating of electrical appliances. This project aims to develop a smart home system by integrating a hardware with IoT system consist of NodeMCU ESP32, relay, voltage and current sensors and the Blynk application to control electrical appliances wirelessly. The energy consumption from the tested electrical loads will be monitored and recorded in Blynk. The results show that the project was successful and have the ability to switch ON or OFF electrical appliances connected to the system wirelessly without having to be in the same places. The observed power consumption that is recorded will be calculated to acquire the electricity bill’s information. This project will help in solving the energy wasted issue and monitoring of electrical appliances became easier.